2021
DOI: 10.3389/fmicb.2021.723322
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Stock Variants of the Archetype Silver Resistance Plasmid pMG101 Demonstrate Plasmid Fusion, Loss of Transmissibility, and Transposition of Tn7/pco/sil Into the Host Chromosome

Abstract: Salmonella Typhimurium carrying the multidrug resistance (MDR) plasmid pMG101 was isolated from three burns patients in Boston United States in 1973. pMG101 was transferrable into other Salmonella spp. and Escherichia coli hosts and carried what was a novel and unusual combination of AMR genes and silver resistance. Previously published short-read DNA sequence of pMG101 showed that it was a 183.5Kb IncHI plasmid, where a Tn7-mediated transposition of pco/sil resistance genes into the chromosome of the E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Interestingly, all pKPC-CAV1321-positive ST38 genomes co-harbored the IncHI2 plasmid. The IncHI2 replicon has been associated with human and animal disease, representing a threat in the context of One Health (Hooton et al, 2021) and, although abundant among Enterobacteriaceae (Wong et al, 2016; Matamoros et al, 2017; Zhao et al, 2018), the IncHI2 had never been reported in ST38 and is rare among other ExPEC strains (Shaik et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, all pKPC-CAV1321-positive ST38 genomes co-harbored the IncHI2 plasmid. The IncHI2 replicon has been associated with human and animal disease, representing a threat in the context of One Health (Hooton et al, 2021) and, although abundant among Enterobacteriaceae (Wong et al, 2016; Matamoros et al, 2017; Zhao et al, 2018), the IncHI2 had never been reported in ST38 and is rare among other ExPEC strains (Shaik et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneity in bacterial laboratory strains and plasmids has been observed many times and we are at a stage when even the same E. coli K-12 stock strains can produce different outcomes, calling reproducibility into question [27,48,[56][57][58][59]. It is clear that there are significant major differences between K-12 and other commensal E. coli strains, and these differences became fixed in the ancestors of the very widely used MG1655 and W3110 strains.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity in bacterial lab strains and plasmids has been observed many times and we are at a stage when even the same E. coli K-12 stock strains can produce different outcomes, calling reproducibility into question (27,48,(56)(57)(58)(59). It is clear that there are significant major differences between K-12 and other commensal E. coli strains, and these differences became fixed in the ancestors of the very widely used MG1655 and W3110…”
Section: Discussionmentioning
confidence: 99%